Analysis of Repurchase Intentions for Organic Products in Generation Y on Batam City - Purwianti, Lily; Iman, R Iqratul (Jurnal Social Economic of Agriculture, 2023)
Healthy living has become one of people's choices in carrying out their lives for the better. There are many ways to live a healthy life, one of which is by consuming organic rice which is proven to have very high nutritional value. However, with so many benefits, the repurchase rate of organic rice is still relatively low. So, in this study, we will analyze how consumers in Batam City are interested in buying organic rice again. The population used in this study was Generation Y, aged between 27-42 years, totaling 384 samples. This study uses the variable perceived enjoyment as an independent variable which is rarely used by other researchers, mainly mediated by the attitude variable which can affect the dependent variable, namely repurchasing intention. As a development of attitude marketing management studies will be influenced by other independent variables such as health benefits, subjective norms, satisfaction, and trust. From the results of this study, the variables studied are important factors that can influence customers in making decisions to re-purchase organic rice by Generation Y in Batam City